1997
DOI: 10.3354/meps159165
|View full text |Cite
|
Sign up to set email alerts
|

In situ swimming speeds of the late pelagic larvae of some Indo-Pacific coral-reef fishes

Abstract: S\~lmrnlng speeds of the late-stage, pelaglc larvae of coral-leef flshes were measured in situ near Llzard Island on Australia's Great Barrler Reef, and Ranglroa Atoll, Tuamotu Islands, French Polynes~a d u n n g 1995-96 Larvae were captured w~t h llght traps and crest nets, and released indiv~du-ally In open water They were then followed by SCUBA d~v e r s , normally for 10 mm, and their speed was measured w~t h a m o d~f~e d plankton-net flow meter and a stop watch Swlmmlng speeds of 260 lalvae of 50 specles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
178
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(185 citation statements)
references
References 12 publications
6
178
0
1
Order By: Relevance
“…tidal flows, surface and subsurface currents and circulation) and active larval behaviour through horizontal and vertical movements (e.g. swimming, buuyancy control) (for fish see Boehlert and Mundy, 1988;Sponaugle and Cowen, 1997;Leis and Carson-Ewart, 1997;Forward et al, 1999;Epifanio and Garvine, 2001 and for crustaceans see Phillips, 1981;Sulkin, 1990;Young, 1995;Forward et al, 1997;Epifanio and Garvine, 2001). Interaction with water motion occurs at a range of scales, from near-substratum flow, which may influence the settlement process (centimetres-metres) (Butman, 1987;Breitburg et al, 1995) to Langmuir circulation and Ekman transport, tidal currents, internal waves, fronts, eddies and upwelling (100s metres-100s kilometres) (Phillips, 1981;Kingsford, et al, 1991;Shanks, 1995;Werner et al, 1997).…”
Section: Movements Of Eggs and Larvaementioning
confidence: 99%
See 1 more Smart Citation
“…tidal flows, surface and subsurface currents and circulation) and active larval behaviour through horizontal and vertical movements (e.g. swimming, buuyancy control) (for fish see Boehlert and Mundy, 1988;Sponaugle and Cowen, 1997;Leis and Carson-Ewart, 1997;Forward et al, 1999;Epifanio and Garvine, 2001 and for crustaceans see Phillips, 1981;Sulkin, 1990;Young, 1995;Forward et al, 1997;Epifanio and Garvine, 2001). Interaction with water motion occurs at a range of scales, from near-substratum flow, which may influence the settlement process (centimetres-metres) (Butman, 1987;Breitburg et al, 1995) to Langmuir circulation and Ekman transport, tidal currents, internal waves, fronts, eddies and upwelling (100s metres-100s kilometres) (Phillips, 1981;Kingsford, et al, 1991;Shanks, 1995;Werner et al, 1997).…”
Section: Movements Of Eggs and Larvaementioning
confidence: 99%
“…Leis and Carson-Ewart (1997) followed (using SCUBA) individual larvae of coral reef fish on the Great Barrier Reef and recorded their direction, depth and speed every 30 seconds. The authors found that there were inherent difficulties in visually tracking underwater since human observers have limited mobility in water compared to larval fish, with fish swimming speeds ranging from ~2 to 65 cms −1 and occasional rapid bursts of acceleration (Leis and Carson-Ewart, 1997). Underwater visual tracking is also limited to studies of animals that inhabit calm, clear and warm waters.…”
Section: Eggs and Larvaementioning
confidence: 99%
“…After this initial 'passive' period, larvae were assumed to enter an 'active' stage during which they are able to swim strongly enough to approach a reef (Stobutzki & Bellwood 1994Leis & Carson-Ewart 1997;Wolanski et al 1997). A baseline passive period of 14 days was used, as would apply for P. amboinensis (Fisher et al 2000).…”
Section: (B) Biological Assumptionsmentioning
confidence: 99%
“…40 body lengths (BL) s -1 . Leis et al (1996) and Leis & Carson-Ewart (1997) also recorded high swimming speeds, with capturerelease methods recording speeds of > 60 cm s -1 for reef fish larvae in the field. These speeds were maintained for several minutes.…”
Section: Introductionmentioning
confidence: 99%